Tuning Methods of PID Controller for DC Motor Speed Control - Ashwaq Abdulameer; Marizan Sulaiman; MSM Aras; Dawood Saleem (Institute of Advanced Engineering and Science, 2016)
The traditional PID controllers are used for a long time to control the DC motor for many industrial processes, that because of the simplicity, flexibility, and satisfactory performance of this type of controller. This paper discusses the basic PID tuning method (Ziegler-Nichols) and its modification (Chien-Hrones-Reswick). Also, analysis the speed control DC motor response using the PID controller parameters that result from the tuning methods mentioned earlier. Moreover, explain the advantage and disadvantage of each formula of these methods. GUL/MATLAB windows used to implementing both methods to create more comfortable and friendly environment for better understanding of the PID controller tuning methods formula for engineering students and practicing engineers.